A Pied Crow Corvus albus survey covering 4 000 km2 of the Karoo: Autumn 2015 - Fincham, John E; Nupen, Peter (Biodiversity Observations, 2016)
Since Pied Crows are numerous and widespread, and can kill so many tortoises, it is logical that they must be capable of inflicting serious damage on other vulnerable prey species